Labirintos da linguagem: um estudo das propagandas alusivas ao sexo feminino numa perspectiva historiográfica - Santos, Jefferson Lucena dos (2013)
This research focuses on the Brazilian advertisements alluding to female historiographical perspective. For this, we focus on postulates Historiography Language that is presented by Konrad Koerner, as a way of rewriting the facts of history knowledge about the language. As our research follows a line of historiography, it is extremely important we adopt the koernerianos principles: contextualization, immanence and adequacy. The main concern about this research is the advertisements portraying the female. We decided to select only those advertisements that refer to the women in the media, having as one of the objectives the expansion of the imagination and understanding cultural and historical female historiographical perspective. Furthermore, we chose that the corpus called non-metalinguistic advertisements consists of verbal language and nonverbal. Thus, for the study of first language, verbal, follow the principles of HL. For the second study, nonverbal, observe the following categories: audience, colors and layout of images, always looking for the relationship between the two languages. In studying the language, regardless of a document linked to visual verbal, from a historiographical perspective, it is necessary to take into account the changes in time, resulting from internal and external factors. These factors, slow and discontinuous, end up being generated by sociocultural and historical influences, this way being responsible for the linguistic changes. Therefore, from this conception that extralinguistic factors are responsible for the progress of the language it is necessary to stick us the linguistic organization particularly to spelling, vocabulary and syntax present in ads in order to observe how the language of advertisements dialogues with linguistic knowledge of the time